Building characters using local wisdom in ngaras and siraman traditions of Sundanese weddings - Sutrisna Wibawa; Yatun Romdonah Awaliah (LPMPP Universitas Negeri Yogyakarta, 2023)
Nowadays, many people are attracted to almost extinct traditions, such as Ngaras and Siraman, in Sundanese weddings. Prominent figures, celebrities, actresses/actors, and ordinary people have re-implemented these traditions, but only a few know the content and local wisdom of the practices. This study aimed to examine Ngaras and Siraman and explore the local wisdom values of the traditions used to build students' character through education. The research method used was descriptive-qualitative analysis. Data were collected through literature and documentation review. The analysis revealed that Ngaras and Siraman are rituals done before akad nikah (marriage covenant). There are values of Sundanese local wisdom presented by the traditions when viewed from the practice, meaning, and function. First, the values are Trisilas(Three Bases), Catur Jati Diri Insani (Superior Human), and Gapura Pancawaluya (the Gate of Five Pillars of Completeness). Second, these values serve as good moral practices related to someone's relationships with God, himself, other human beings, nature, and time. Third, such values form moral functions to pursue further implementation of ethno-pedagogy in school.